HUBUNGAN PERSEPSI TENTANG MENOPAUSE DENGAN TINGKAT KECEMASAN PADA WANITA YANG MENGHADAPI MENOPAUSE - Christiani, -; Retnowati, Sofia; Purnamaningsih, Esti Hayu (Faculty of Psychology, Universitas Gadjah Mada, 2000)
The aim of the research was to investigate the relationship between womenâ€™s perception of menopause and their level of anxiety. Subjects were members of â€œDharma Wanitaâ€ UGM. The research used Perception Scale to measure menopause perception, and Taylor Manifest Anxiety Scale (TMAS) to measure anxiety. Data analysis was done by using Product Moment Correlation analysis. This study found that was a significant negative correlation between perception of the menopause and level of anxiety. The correlation indicated that the more positive perception of menopause, the lower level of anxiety; the more negative perception of menopause, the higher level of anxiety. Keywords: menopouse, anxiety